Efektivitas Gel Ekstrak Etanol Daun Awar-Awar (Ficus septica Burm. F) Terhadap Penyembuhan Luka Bakar Pada Kelinci (Oryctolagus cuniculus) - Andi Ulfah Magefirah Rasyid; Dewi Isnaeni; Syafruddin Syafruddin; Zulkifli Zulkifli (Jurnal Kesehatan Farmasi, 2022)
A study on the effectiveness of Awar-awar (Ficus septica Burm. F) Leaf Ethanol Extract Gel on Healing Burns in Rabbits (Oryctolagus cuniculus). Most effective against burn wound healing in rabbits (Oryctolagus cuniculus). Awar-awar leaf extract (Ficus septica Burm. F) was prepared in a gel with a concentration of 1.5% w/v, 2% w/v, and 2.5% w/v. This study used rabbits as test animals; rabbits were divided into five groups. In each group, two rabbits had burns on their backs. The rabbit's back was burned with an area of 2.5 cm. Brushing is done twice a day. Observations were made with wound size parameters on the 1st, 3rd, 6th, 9th, and 12th days. The results showed that the gel preparation of awar-awar leaf extract (Ficus septica Burm. F) concentration of 2.5 % w/v was the most effective for wound healing in rabbits, with an average value of 0.75 cm. However, the effect was still lower than that of BioplacentonÂ® gel as a positive control with an average value of 0.5 cm.